Neutropenia Occurs More Often Under Carbimazole than Under Methimazole Treatment in Pediatric Graves' Disease Patients. - Schempp, Vera; Cebeci, Ayse Nurcan; Reinauer, Christina; Woelfle, Joachim; Dörr, Helmuth Günther; Roosen, Marie Thérèse; Gohlke, Jonas; Gohlke, Bettina (Thyroid, 2024)
Background: Agranulocytosis is a rare antithyroid drug treatment (ATD) side effect seen in children suffering from Graves' disease (GD). Neutropenia is a recognized adverse event associated with ATD but has also been reported as pre-treatment neutropenia in GD. Methods: We performed a retrospective cohort study to analyze the longitudinal clinical and biochemical data of 161 pediatric patients with GD who received either methimazole (MMI) or carbimazole (CBZ) as ATD. The inclusion criteria were elevated free thyroxine (fT4 >25 pmol/L), suppressed thyrotropin (TSH <0.05 mlU/mL), and elevated thyrotropin receptor antibodies (TSHRAbs >2.5 IU/L). Absolute neutrophil count (ANC) was used to define neutropenia (ANC <1800/µL) and agranulocytosis (ANC <500/µL). Results: Nine of the 161 patients had neutropenia at diagnosis (ANC: 1348/µL ± 250) without further deterioration under ATD. In this subgroup, we found higher levels of free triiodothyronine (fT3: 31.45 pmol/L ± 3.99) at diagnosis in comparison with those who developed neutropenia (26.29 pmol/L ± 12.96; p = 0.07) and those without neutropenia before and during therapy (23.12 pmol/L ± 13.7; p = 0.003). Thirty-eight patients (23.6%) became neutropenic (ANC: 1479/µL ± 262) while receiving ATD. Neutropenia occurred after a mean of 551.8 (range: 10-1376) days, mostly without further deterioration. Two of these 38 patients developed agranulocytosis and underwent emergency thyroidectomy. The patients with neutropenia were significantly younger (p = 0.031). Neutropenia occurred significantly more often in patients receiving CBZ (50%; n = 20/40) than in those receiving MMI (16.5%; n = 18/110; p = 0.001). The minimum ANC was significantly lower in the CBZ (1971/µL ± 1008) than in the MMI group (2546 ± 959); p = 0.004. Conclusions: Neutropenia occurred significantly more often under CBZ than MMI. As this is potentially due to higher immunogenicity, we suggest that children with GD should be treated with MMI. Frequent measurements of ANC may be needed to detect severe agranulocytosis, although low pre-treatment ANC may not necessarily be a contraindication to ATD treatment. Young age may be potentially associated with an increased risk of reduced ANC. Further investigation is necessary to fully understand risk factors for neutropenia in children with GD.
EVALuna2:567377